SCIENTIFIC, PEDAGOGICAL AND SOCIAL A. I. KUKHTENKO AT THE KIEV INSTITUTE CIVIL AVIATION ENGINEERS - Azarskov, V. N.; Shevelev, A. G. (Problems of Informatization and Management, 2021)
Throughout his long life, the scientific and pedagogical activities of A.I. Kukhtenko took place not only in KNIGA, but also in other organizations and institutions. This is described in detail and reflected in the essay on his life and work [1]. The multifaceted and fruitful scientific and pedagogical activity of A.I. Kukhtenko at the Institute of Civil Aviation Engineers as a professor, head of the department, vice-rector for scientific work, scientific director of several industry research laboratories.